Relationship between buprenorphine adherence and relapse, health care utilization and costs in privately and publicly insured patients with opioid use disorder - Ronquest NA; Willson TM; Montejano LB; Nadipelli VR; Wollschlaeger BA (Dove Medical Press, 2018)
Naoko A Ronquest,1 Tina M Willson,2 Leslie B Montejano,2 Vijay R Nadipelli,1 Bernd A Wollschlaeger3 1Global Health Economics and Outcomes Research, Indivior Inc., Richmond, VA, USA; 2Outcomes Research, Truven Health Analytics®, Part of the IBM Watson Health™ Business, Cambridge, MA, USA; 3Aventura Family Health Center, Miami, FL, USA Background: Treatment for opioid use disorder is important because of the negative health, societal and economic consequences of illicit opioid use, but treatment adherence can be a challenge. This study assessed the association between buprenorphine medication-assisted treatment (MAT) adherence and relapse, health care utilization and costs.Patients and methods: Patients with opioid use disorder who were newly initiating a buprenorphine MAT regimen were identified in the 2008–2014 MarketScan® Commercial and Medicaid Databases and followed for 12 months after their earliest outpatient pharmacy claim for buprenorphine. Adherence was categorized using proportion of days covered (PDC) with buprenorphine, and patients with PDC≥0.80 were classified as adherent. Descriptive and adjusted analyses compared relapse prevalence, utilization and costs, all measured in the 12 months following buprenorphine MAT initiation, of adherent patients to patients in non-adherent PDC categories (PDC<0.20, 0.20≤PDC<0.40, 0.40≤PDC<0.60, 0.60≤PDC<0.80).Results: Adherent patients were 37.1% of the Commercial sample (N=16,085) and 41.3% of the Medicaid sample (N=5,688). In both samples, non-adherent patients were significantly more likely than adherent patients to relapse and to have hospitalizations and emergency department visits. As a result, as buprenorphine MAT adherence increased, pharmacy costs increased, but medical costs decreased. Total costs (pharmacy plus medical costs) in the 12 months following buprenorphine MAT initiation decreased with adherence in Commercial patients ($28,525 for PDC<0.20 to $17,844 for PDC≥0.80). A slight decrease in total costs in the 12 months following buprenorphine MAT initiation was also observed in Medicaid patients ($21,292 for PDC<0.20 to $18,621 for PDC≥0.80). After adjustment, total costs of adherent patients in the Commercial sample ($17,519) were significantly lower compared with those of non-adherent patients (range $20,294–$24,431). In the Medicaid sample, adjusted total costs were not significantly different between adherence groups.Conclusion: Buprenorphine MAT adherence in the 12 months following treatment was associated with reduced odds of relapse and reduced unadjusted medical costs. For Commercial patients who were adherent to treatment, the adjusted total costs were predicted to be 30% lower than those for patients with PDC<0.20. Keywords: buprenorphine, adherence, opioid use disorder, relapse, utilization, costs